Sediment Spatial Distribution and Quality Assessment of Metals in Chinook Salmon and Resident Killer Whale Marine Habitat in British Columbia, Canada - Kim, Joseph J.; Delisle, Kelsey; Brown, Tanya M.; Ross, Peter S.; Noël, Marie (Archives of Environmental Contamination and Toxicology, 2023)
At-risk resident killer whale (Orcinus orca) populations of the northeastern Pacific, Canada, and their main prey, Chinook Salmon (Oncorhynchus tshawytscha), are exposed to a variety of contaminants including chemical elements from both natural and anthropogenic sources, which may be constraining their recovery. Concentrations of 36 chemical elements in subtidal surface sediments (1–435 m depth) collected from 98 sites along the British Columbia coast were used to characterize coast-wide patterns, and a subset of metals (mercury (Hg), cadmium (Cd), arsenic (As), nickel (Ni), copper (Cu), and lead (Pb)) were selected to assess Chinook Salmon and resident killer whale marine habitat quality. Principal component analysis (PCA) showed a dominance of Hg, antimony (Sb), Pb, Cu, and zinc (Zn) for Prince Rupert Harbour, Victoria Harbour, and Burrard Inlet, suggesting local sources. Based on the PCA, geochemical properties such as total organic carbon (TOC), acid volatile sulfide (AVS), and pH explained the spatial distribution of all elements in sediment (p < 0.001). Mercury, Cd, As, Ni, Cu, and Pb hotspots were identified along the coast of Vancouver Island, the central and north coast, in the Strait of Georgia, and Haida Gwaii. Bischof Island of Haida Gwaii and Ardmillan Bay on the central coast were most contaminated and enriched by Cd, determined by geoaccumulation index (Igeo) and enrichment factor (EF), respectively. Marine habitat quality was assessed by comparing metal concentrations to Canadian Sediment Quality Guidelines (SQGs). Chinook Salmon populations may be indirectly affected by metal toxicity (As > Cd and Cu > Ni > Hg > Pb) to lower trophic level prey species. Toxicity related impacts to benthic organisms as a result of exposure to elevated Cd and As concentrations in Northern Resident Killer Whale critical habitat and to Hg, Cd, As, Ni, Cu, and Pb concentrations in Southern Resident Killer Whale critical habitat may indirectly pose a threat to resident killer whale populations, highlighting a need for management actions to reduce risks associated with these metals.